Isolasi dan Pemindah Biakan Bakteri dari Sampel Air Sumur sebagai Upaya Identifikasi Mikroorganisme Lingkungan - Aulia Ramadhani; Ardi Mustakim (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aimed to isolate and culture bacteria from well water samples as a first step in identifying microorganisms found in domestic water environments. Well water was chosen because it is one of the main water sources for communities, especially in rural areas, but is highly susceptible to contamination due to human activities such as household waste, agricultural waste, and poor sanitation systems. The isolation process was carried out using the pour plate and scratch plate methods using Nutrient Agar (NA) and MacConkey Agar (MAC) media, which function to detect various types of bacteria, both pathogenic and non-pathogenic, including gram-positive and gram-negative bacteria. Samples were incubated at 37°C for 24–48 hours to allow colony growth. After the incubation period, the growing colonies were observed morphologically based on the color, shape, and edge of the colonies. Next, the colonies were cultured to obtain pure cultures for further analysis. Preliminary results showed a diversity of colony shapes indicating the presence of several bacterial species, such as Escherichia coli, Pseudomonas sp., and possibly Enterobacter sp., which are indicators of air quality and the level of fecal contamination. This study provides a preliminary overview of the microbiological status of well water and the importance of regular testing of domestic water sources. Early identification through isolation and culture is crucial for mitigating public health risks and providing a basis for any necessary air treatment or sanitation interventions. Therefore, the results of this study are expected to serve as a reference for the community and government in sustainably maintaining the quality and safety of well water. The recommended next step is to conduct antibiotic resistance testing to determine the potential hazards of the identified pathogenic bacteria.